2000
DOI: 10.1002/biof.5520130127
|View full text |Cite
|
Sign up to set email alerts
|

Recent topics in anti‐oxidative factors

Abstract: Lipids and anti-oxidative factors regulate immune functions such as immunoglobulin production and chemical mediator release. For example, polyunsaturated fatty acids (PUFA) enhance IgE production of isolated rat lymphocytes, but not in the presence of alpha-tocopherol. In addition, anti-oxidative factors such as tea polyphenols and flavonoids exert inhibitory effect on chemical mediator release from rat peritoneal exudate cells (PEC). Some of these immunoregulatory activities of food components could be expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Our results indicate that these phenolic compounds may not be the main anti-allergic active components in adlay bran (Table 3). However, it has been reported that there is no correlation between anti-allergic and anti-oxidative effects (Yamada and Tachibana, 2000). In addition, the complement activation pathway may serve as a central regulator of allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that these phenolic compounds may not be the main anti-allergic active components in adlay bran (Table 3). However, it has been reported that there is no correlation between anti-allergic and anti-oxidative effects (Yamada and Tachibana, 2000). In addition, the complement activation pathway may serve as a central regulator of allergic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The tocopherols act as chain-breaking antioxidants that protect cell membranes from damage caused by lipid peroxidation and also inhibit cell proliferation, platelet adhesion and formation of N -nitroso compounds 4 , 5 . Both the carotenoids and tocopherols stimulate cell-mediated and humoral immunity 6 .…”
mentioning
confidence: 99%
“…The polyphenols in SBB have been shown to be involved in its antioxidant activity ( Chen et al, 2007 , 2013 ). For example, epigallocatechin gallate, a polyphenol abundant in green tea, has shown antioxidant activity and strong antiallergic effects ( Yamada and Tachibana, 2000 ). Yamada et al (1999) reported that the antioxidant activity of phenolic compounds is involved in the inhibitory activity of LTB 4 production by mast cells.…”
Section: Discussionmentioning
confidence: 99%